Feeding Strategies to Reduce Nutrient Losses and Improve the Sustainability of Growing Pigs - Pomar, Candido; Andretta, Ines; Remus, Aline (Frontiers in Veterinary Science, 2021)
The efficiency of pig production using nutrients has increased over the years. Still, better nutrient efficiency of utilization can be achieved by feeding pigs with diets adjusted to their estimated requirements. An increase in nutrient efficiency of utilization represents economics gains while maximizing environmental performance. The objective of this paper is to review the impact of different methods of diet formulation that provide farm animals with the amount of nutrients to satisfy their needs while minimizing nutrient excretion and greenhouse gas emissions. Diet formulation is one tool that can help to maximize nitrogen and energy utilization by decreasing crude protein content in diets. The use of local feedstuff and non-human edible products (e.g., canola meal) associated with synthetic amino acid inclusion in the diet are valuable techniques to reduce carbon footprint. Another powerful tool that allows not only daily tailor diets for maximal nutrient efficiency of utilization but to reduce costs and improve nitrogen efficiency of utilization is precision feeding and nutrition. In this review, we simulated through mathematical models the nitrogen and energy efficiency of utilization resulting from the crude protein reduction in the diet. An 8% crude protein reduction in the diet can increase nitrogen efficiency of utilization by 54% while costing 11% less than a control diet without synthetic amino acids. The same reduction in crude protein represented a major improvement in available energy, due to the decrease of energetic losses linked to protein deamination. Urinary and hindgut fermentation energy losses were 24% lower for pigs fed with low protein diets when compared to control diets. In terms of modern feeding techniques strategies, precision feeding and nutrition can decrease nitrogen excretion by 30% when compared to group phase-feeding. The benefits of feeding pigs with low-protein diets and precision feeding techniques are additive and might result in a 61% nitrogen efficiency of utilization. There is room for improvement on the way nutrient requirements are estimated in pigs. Improving the understanding on the variation of nutrient utilization among pigs can contribute to further environmental gains.